Strengthening the pay for performance link in government pay for performance - Jamaiudin, Norhaslinda (LAP LAMBERT Academic Publishing, 2012)
This study aims to examine the relationship between pay and performance with special focus on the Malaysian Remuneration system (MRS). The MRS which was introduced in 2002 continued to weigh in the performance aspect as the main indicator in evaluating employees' achievement.